2004
DOI: 10.1074/jbc.m402320200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human TRPC6 Channels by Receptor Stimulation

Abstract: The human TRPC6 channel was expressed in human embryonic kidney (HEK) cells, and activity was monitored using the giga-seal technique. Whole cell membrane currents with distinctive inward and outward rectification were activated by carbachol (CCh) in TRPC6-expressing cells, but not in lacZ-transfected controls. The effect of CCh was steeply dose-dependent with a K 0.5 of ϳ10 M and a Hill coefficient of 3-4. A steep concentration-response relationship was also observed when TRPC6 activity was measured using a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 42 publications
4
49
1
Order By: Relevance
“…Carbachol is capable of inducing ROCE by activating and promoting cell surface expression of TRPC6 downstream of muscarinic receptor binding (26,27). Although the suspected change in its mRNA could not be validated, TRPC6 seemed a logical candidate and may be involved in some manner we did not detect (23,24).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Carbachol is capable of inducing ROCE by activating and promoting cell surface expression of TRPC6 downstream of muscarinic receptor binding (26,27). Although the suspected change in its mRNA could not be validated, TRPC6 seemed a logical candidate and may be involved in some manner we did not detect (23,24).…”
Section: Discussioncontrasting
confidence: 42%
“…RGS proteins are GTPase-activating proteins that enhance G␣-GTP hydrolysis, thereby decreasing the lifetime of active states of G protein subunits, and RGS4 is expressed in ␤ cells (22). TRPC6 has been reported to be a receptor-operated cation channel that is activated upon GPCR stimulation and subsequent phospholipase C ␤ activation (23,24). Calcium entry occurring through plasma membrane channels as a result of GPCR activation independent of the state of Ca 2ϩ i stores is referred to as ROCE (25).…”
Section: Carbachol-induced Changes In Camentioning
confidence: 99%
“…Since the actual mechanism of activation of TRPC3 channels by DAG remains unknown, the reason for this difference is not clear. We and others also have shown that activation of TRPC6 by exogenous DAG is less than that observed with receptor stimulation (6,13), and it has been suggested that DAG may act indirectly to activate TRPC3 channels (31). Although it seems clear that exogenous DAG is not equivalent to receptor-mediated activation, there is good correlation between the extent of TRPC3 channel activation and the subsequent transepithelial Ca 2ϩ flux in the IMCD-3 cell model system.…”
Section: Discussionmentioning
confidence: 94%
“…There are seven members of the mammalian TRPC family, designated TRPC1-TRPC7, all of which are activated downstream of PLC (22). Although the ability of TRPC proteins to function as native store-operated channels remains highly controversial (5,24,35), it is well established that TRPC3, TRPC6, and TRPC7 can be activated by DAG analogs (6,10,23,24,33), but the molecular basis for this activation remains unknown.Our previous studies have shown that TRPC3 and TRPC6 are expressed in principal cells of the collecting duct (CD) along with the water channel, aquaporin-2 (AQP2) (7,8). When examined in normally hydrated rats, all three channels are predominantly localized to cytoplasmic vesicles.…”
mentioning
confidence: 99%
“…The general consensus is that TRPC6 forms a ROC that is directly activated by DAG, and is insensitive to activation by IP 3 and Ca 2+ store depletion (Boulay et al 1997;Estacion et al 2004;Zagranichnaya et al 2005;Zhang et al 2006). Although TRPC6 is a member of the TRPC3/6/7 subfamily it shows distinct functional and structural properties.…”
Section: Trpc6mentioning
confidence: 99%